Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae) - Raha, Sujoy; Das, Sunandan; Bag, Probhat; Debnath, Sudipta; Pramanick, Kousik (Zootaxa, 2018)
We describe a new species, Trachischium sushantai sp. nov., from Jammu, India. The new species can be distinguished from its congeners by a combination of the following characters: —a single nasal, a singleprefrontal, a single post-ocular, 13 rows of dorsal scales at mid-body, 152 ventrals, 23 pairs of subcaudals and those on anterior half of tail as long as wide and regular hexagon or rhomboid shaped, uniformly dark brown dorsum and brown subcaudals, edged incream or yellow posteriorly. The new species closely resembles T. fuscum. We also provide a redescription of T. fuscum and comments on its subjective synonyms.